New Insights on Astrocyte Ion Channels: Critical for Homeostasis and Neuron-Glia Signaling - Olsen, Michelle L.; Khakh, Baljit S.; Skatchkov, Serguei N.; Zhou, Min; Lee, C. Justin; Rouach, Nathalie (SOC NEUROSCIENCE, 2015)
Initial biophysical studies on glial cells nearly 50 years ago identified these cells as being electrically silent. These first studies also demonstrated a large K+ conductance, which led to the notion that glia may regulate extracellular K+ levels homeostatically. This view has now gained critical support from the study of multiple disease models discussed herein. Dysfunction of a major astrocyte K+ channel, Kir4.1, appears as an early pathological event underlying neuronal phenotypes in several neurodevelopmental and neurodegenerative diseases. An expanding list of other astrocyte ion channels, including the calcium-activated ion channel BEST-1, hemichannels, and two-pore domain K+ channels, all contribute to astrocyte biology and CNS function and underpin new forms of crosstalk between neurons and glia. Once considered merely the glue that holds the brain together, it is now increasingly recognized that astrocytes contribute in several fundamental ways to neuronal function. Emerging new insights and future perspectives of this active research area are highlighted within.
Keywords: RECTIFYING K+ CHANNEL; AMYOTROPHIC-LATERAL-SCLEROSIS; GLUTAMATE UPTAKE; POTASSIUM CHANNELS; TONIC INHIBITION; NERVOUS-SYSTEM; SPINAL-CORD; HIPPOCAMPAL ASTROCYTES; SENSORINEURAL DEAFNESS; SYNAPTIC-TRANSMISSION